2023
DOI: 10.1186/s12967-023-03899-w
|View full text |Cite
|
Sign up to set email alerts
|

A prediction model for the impact of environmental and genetic factors on cardiovascular events: development in a salt substitutes population

Abstract: Background Cardiovascular disease (CVD) has evolved into a serious public health issue that demands the use of suitable methods to estimate the risk of the disease. As a result, in a sample of individuals who completed a 3-year low-sodium salt or conventional salt intervention in a hypertensive environment, we constructed a 13-year cardiovascular (CV) event risk prediction model with a 10-year follow-up. Methods A Cox proportional hazards model was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…30 Additionally, dietary sodium is a risk factor for hypertension. 31,32 In this study, we combined data from NHANES 2011 to 2012 and 2013−2014 and involved 2276 Americans…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…30 Additionally, dietary sodium is a risk factor for hypertension. 31,32 In this study, we combined data from NHANES 2011 to 2012 and 2013−2014 and involved 2276 Americans…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that high dietary sodium intake might influence cognitive performance 30 . Additionally, dietary sodium is a risk factor for hypertension 31,32 . In this study, we combined data from NHANES 2011 to 2012 and 2013−2014 and involved 2276 Americans (1,670 participants with hypertension) aged ≥60 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation